Handbook for Health Care Ethics Committees - Post, Linda Farber; Blustein, Jeffrey (Book collections on Project MUSE., 2021)
"Responding to the growing need for health care ethics committees to provide members with a solid foundation of knowledge about bioethics and its practical applications, this third edition builds on the format and content of its predecessors with updated, comprehensive, reorganized, and entirely new sections, each of which examines ethics committee functions and suggests ways in which committees can be most effective assets to their institutions. It remains the only book to address the singular challenges and needs of health care ethics committees and their members"--